Georgia Architectural and Historic Properties Survey of Morven [031] Main St. Quitman, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Morven [031] Main St. Quitman, Ga. December 1980. Saddlebag. Rectangular with gabled roof and hipped porch. Square posts. Clapboacrd siding. Double hung sash windows with 2/2 lights. Transom. Set on brick piers. Fair condition.Date of Construction: c. 1910. Not significant as part of a potential National Register historic district. Area not extensive enough historically.
Georgia Architectural and Historic Properties Survey of Morven [031] Main St. Quitman, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.12 MB (1,175,037 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Real property surveys; Brooks County (Ga.); Morven, Ga.; Quitman (Ga.)